The Techniques of Teaching EFL for Preschoolers of Kidsstar Makassar - Khotimah, Khusnul; Dollah, Syarifuddin; Muliati, A. (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
This research aimed to find out The Techniques for Teaching EFL to Preschoolers of Kidsstar Makassar. This study research includes qualitative research with descriptive qualitative. The subjects of the research were three kindergarten teachers of Kidsstar Makassar. The data were collected using an interview. The researchers found that (1) techniques teaching EFL for preschoolers where fun learning includes, phonics, games, music and movement, reading aloud, and storytelling (2) constraints faced by teachers in applying several techniques in teaching EFL for preschoolers where learners lack self-confidence, learners lost controlled when playing games, learners miss understanding with the story, learners didn’t know how to pronounce.